TINJAUAN YURIDIS MODUS OPERANDING TINDAK PIDANA PENCUCIAN UANG (MONEY LAUNDERING) - Fathur Rachman (PRANATA HUKUM, 2019)
ABSTRAK Money laundering is a hot or dirty money laundering practice (dirty money). This dirty money comes from illegitimate and illegal practices such as corruption, bribery, smuggling, as well as banking crimes and other unhealthy practices. To clean it, the money is placed in a bank or certain place for a while before being transferred to another place (layering), for example through the purchase of shares in the capital market, foreign exchange transfers or the purchase of an asset. After that, the offender will receive money that has been cleared from the washing field in the form of income derived from the purchase of shares, foreign exchange or assets (integration). The practice of money laudering that continues to occur along with the times and modernization provides the concept of thinking to examine the legal issue of the regulation being implemented, and how the modus operandi of the occurrence of a case. The stages and mode of occurrence of money laundering crime include: Placement, which is the first stage by placing (depositing) the illicit money into the financial system (financial system). Layering at this stage the washers try to break the money from the crime from the source, by transferring the money from one bank to another, up to several times. Integration, iniuang washed stages are brought back into circulation in the form of net income even as tax objects by using money that has become lawful for business activities. The perpetrator of money laundering as an organized crime, is carried out by a person who controls or has special knowledge in the world of financial service providers. Even they must master science in the field of computers. Money laundering in addition is very detrimental to society, also very detrimental to the State because it can influence or undermining national economic stability or State finances by increasing various crimes